2018
DOI: 10.1055/s-0038-1669938
|View full text |Cite
|
Sign up to set email alerts
|

Dexmedetomidine for Sedation of Neonates with HIE Undergoing Therapeutic Hypothermia: A Single-Center Experience

Abstract: Hypoxic-ischemic encephalopathy (HIE) is a significant cause of morbidity and mortality in neonates. Therapeutic hypothermia reduces the risk of death or disability. Providing optimal sedation while neonates are undergoing therapeutic hypothermia is likely beneficial but may present therapeutic challenges. There are limited data describing the use of dexmedetomidine for sedation in patients undergoing therapeutic hypothermia. The objective of this study is to evaluate the efficacy and short-term safety of dexm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(21 citation statements)
references
References 18 publications
1
20
0
Order By: Relevance
“…Dexmedetomidine, another α 2 -adrenergic agonist commonly used for sedation in intensive care settings, is also effective in inducing thermal tolerance ( 38 ). A single center retrospective study published in 2018 described their experience using dexmedetomidine for sedation in 19 infants with HIE during therapeutic hypothermia who tolerated the drug without significant cardiovascular instability ( 42 ). A 2020 publication reports the pharmacokinetics of dexmedetomidine in 7 infants with HIE during TH ( 15 ) who also tolerated it well.…”
Section: Discussionmentioning
confidence: 99%
“…Dexmedetomidine, another α 2 -adrenergic agonist commonly used for sedation in intensive care settings, is also effective in inducing thermal tolerance ( 38 ). A single center retrospective study published in 2018 described their experience using dexmedetomidine for sedation in 19 infants with HIE during therapeutic hypothermia who tolerated the drug without significant cardiovascular instability ( 42 ). A 2020 publication reports the pharmacokinetics of dexmedetomidine in 7 infants with HIE during TH ( 15 ) who also tolerated it well.…”
Section: Discussionmentioning
confidence: 99%
“…In the periphery, activation of post-synaptic α 2 -adrenergic receptors inhibits lipolysis and non-shivering thermogenesis in brown fat [ 14 , 15 ]. The physiologic effects of α 2 -adrenergic agonists, predominantly dexmedetomidine, on temperature regulation and heat generation have led to its use to prevent shivering following anesthetic care and during therapeutic hypothermia [ 16 - 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Like morphine, the pharmacokinetics of dexmedetomidine are altered such that clearance is reduced by 56% following experimental hypoxia-ischemia and an additional 33% during TH [ 100 ]. A retrospective cohort study identified an effective dose of 0.3 mcg/kg/h (range 0.2–0.5 mcg/kg/h) during TH with no evidence of altered respiratory status, bradycardia, or hypotension at these lower doses [ 101 ]. Further, full enteral feedings were achieved at a mean of 6 days of life, sooner than historic controls treated with fentanyl infusion.…”
Section: Sedation Of the Term Neonate During Therapeutic Hypothermiamentioning
confidence: 99%